2021
DOI: 10.1177/1046878120988895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Digital Serious Games Related to Patient Care in Pharmacy Education: A Systematic Review

Abstract: Background. In recent years, the use of digital serious games in the education of healthcare students and professionals has been frequent. However, there are no high-level evidence studies focused on the effect of this tool in the development of patient care-related competencies in pharmacy education. Aim. To assess the effect of digital serious games on learning about patient care in pharmacy education. Methods. The Cochrane Library, ERIC, Embase, IPA, LILACS, PubMed, Scopus, and Web of Science databases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 91 publications
(173 reference statements)
0
7
0
1
Order By: Relevance
“…Based on SDT, maintaining learners' intrinsic motivation also requires facilitating needs satisfaction (Ryan and Deci, 2017). To date, strategies directed toward trainees' interest have received a significant amount of attention in the professions education literature in the form of serious games and gamification (Wang et al, 2016;Dankbaar, 2017;Rutledge et al, 2018;Gentry et al, 2019;Maheu-Cadotte et al, 2021;Silva et al, 2021;Min et al, 2022).…”
Section: Stands For Confidence: Trainees Must Feel Like They Can Atta...mentioning
confidence: 99%
“…Based on SDT, maintaining learners' intrinsic motivation also requires facilitating needs satisfaction (Ryan and Deci, 2017). To date, strategies directed toward trainees' interest have received a significant amount of attention in the professions education literature in the form of serious games and gamification (Wang et al, 2016;Dankbaar, 2017;Rutledge et al, 2018;Gentry et al, 2019;Maheu-Cadotte et al, 2021;Silva et al, 2021;Min et al, 2022).…”
Section: Stands For Confidence: Trainees Must Feel Like They Can Atta...mentioning
confidence: 99%
“…No Brasil, os jogos educativos vêm sendo comumente utilizados como uma estratégia educativa nas áreas de Medicina e Enfermagem 11,[16][17][18][19][20][21] ; contudo, existem poucos estudos publicados no ensino da Farmácia e são usualmente voltados para o ciclo básico 20,21 . A maioria das experiências com o uso de jogos por estudantes de farmácia é proveniente de estudos internacionais, sobretudo a partir da última década, refletindo a crescente tendência no uso dessa ferramenta educativa 22,23 . Recente estudo multicêntrico conduzido em sete universidades de cinco diferentes países ao redor do mundo indicou o jogo educativo como uma ferramenta potencial para propiciar importantes experiências de aprendizagem, promover a educação interprofissional, reforçar a segurança do paciente, além de preparar os estudantes de Farmácia para a prática futura 24 .…”
Section: A (Re)construção Do Educador Farmacêuticounclassified
“…Studies will also be identified by hand searching the reference lists of previous systematic reviews related to web-based instruction in HPE [38,44,[49][50][51][52][53][54][55][56][57][58].…”
Section: Hand Searchingmentioning
confidence: 99%
“…Although previous reviews have focused on motivational design features of web-based instruction in HPE [38,44,[49][50][51][52][53][54][55][56][57][58], none have sought to (1) achieve the specific goal of using existing evidence to refine models of motivational design, (2) propose which types of evidence will be required to meet this goal, (3) identify the study designs that can generate such evidence (eg, studies comparing motivational design strategies), and (4) appraise the degree to which studies have generated such evidence. Thus, the value of our review lies in its ability to appraise where we have been and to inform where we ought to go.…”
Section: Overviewmentioning
confidence: 99%